OC-067 Phenotyping visceral pain in humans using brain imaging. (23rd September 2015) - Coen, S J; Kano, M; Farmer, A D; Fukudo, S; Aziz, Q
Abstract : Introduction: The human pain experience integrates concepts such as sensation, cognition and emotion. This complex combination of factors contributes to inter-individual variation in pain reporting which reduces the validity of experimental studies, limiting our understating of pain. Our investigations have assessed psychological, physiological and brain processing of visceral pain in a large group of healthy volunteers to characterise homogenous subgroups (phenotypes) within the normal healthy population. Methods: Initially we evaluated personality traits, autonomic and HPA axis activity in 120 healthy volunteers during painful oesophageal stimulation (OS) and demonstrated the presence of two phenotypic profiles. Phenotype A are characterised by the personality trait extraversion, greater pain tolerance and increased sympathetic activity to OS. Phenotype B are more neurotic, have reduced pain tolerance and increased parasympathetic activity during OS. Using the findings of our initial study, a subgroup of volunteers (13 male, 13 phenotype A, 13 phenotype B) were recruited for a functional magnetic resonance imaging (fMRI) study. Volunteers received twenty phasic painful distensions to the distal oesophagus at pain toleration threshold. Pain perception ratings were recorded following each distension using a visual analogue scale (VAS). Brain activity during the painful OS was measured using fMRI and compared between groups. Results: All volunteers rated the OS as painful ((mean VAS +SEM) 64.3+2.2). During painful oesophageal stimulation both groups activated a matrix of brain regions including the insula, anterior cingulate cortex, thalamus and frontal cortex. Comparison of phenotype A vs Phenotype B revealed a difference in brain processing between the two groups in the left thalamus (P=0.01), right anterior insula (P=0.01) and right frontal cortex (P=0.002) where phenotype A demonstrated significantly more activity in all regions. Conclusion: Through a series of studies we provide evidence for the existence of two phenotypic responders to visceral pain. We have shown differences in autonomic and brain processing of pain between the two phenotypes and therefore identified a source of inter-individual variability in healthy subjects. Sympathetic predominant response to visceral pain (phenotype A) is associated with an increase in a previously described interoceptive sympathetic pathway in the brain.1 Finally, our data suggest the existence of two homogenous groups which may have implications for volunteer selection in future studies investigating pain.